تغيرات الخلايا البطانية القرنية عند المرضى الحسيرين المستخدمين للعدسات اللاصقة الطرية - Darwish, Taym (Latakia University Journal -Medical Sciences Series, 2019)
تغيرات الخلايا البطانية القرنية عند المرضى الحسيرين المستخدمين للعدسات اللاصقة الطرية Aim: To determine changes in corneal endothelial cell morphology in myopic Syrian patients wearing soft contact lenses for 6 month at least. Methods: 35 patients wearing soft contact lenses and 35 patients wearing glasses participated in the study. Corneal endothelial cells morphology (endothelial cell density, coefficient of variation in cell area, and percent of hexagonality) was evaluated using specular microscope. Results: The mean endothelial cell density was 2808 and 2862 for the wearing soft contact lenses group and the control group respectively (p=0.4). The mean coefficient of was 31.1 and 30.7 respectively (p=0.6). the percent of hexagonality was 59.7 and 60.6 respectively (p=0.5). Conclusion: Daily wear of soft contact lenses for 6-36 months does not cause corneal enodothelial morphological changes in a sample of Syrian patients. This is probably due to lens high oxygen transmission and short wearing period. الهدف: تحديد التغيرات بشكل خلايا بطانة القرنية لدى المرضى الحسيرين السوريين الذين يرتدون عدسات لاصقة طرية لمدة 6 أشهر على الأقل. الطرق: شارك بالدراسة 35 مريض يرتدون العدسات اللاصقة الطرية و 35 مريض يستخدمون النظارات (مجموعة الشاهد). تم تقييم شكل خلايا البطانة القرنية (متوسط كثافة الخلايا , معامل تغير حجم الخلايا , نسبة الخلايا السداسية) بواسطة المجهر المرآوي. النتائج: كان متوسط كثافة الخلايا البطانية 2808 خلية/ملم² في مجموعة مستخدمي العدسات اللاصقة و 2862 خلية/ملم² في مجموعة الشاهد (p=0.4). كان معامل تغير حجم الخلايا % 31.1و % 30.7على التوالي (p=0.6) و نسبة الخلايا السداسية كانت 59.7 و 60.6 على التوالي (p=0.5) الاستنتاج: إن الاستخدام اليومي للعدسات اللاصقة الطرية لمده 6-36 شهر لا يسبب تغيرات شكلية في الخلايا البطانية القرنية لدى عينة من المرضى السوريين, قد يكون ذلك بسبب نفوذية العدسة العالية للأكسجين و قصر فترة استخدام العدسات اللاصقة